1930
DOI: 10.1002/jlac.19304780111
|View full text |Cite
|
Sign up to set email alerts
|

Über die Druckhydrierung des Cinchonins und das Bz‐Tetrahydrochinolin. (V. Abhandlung über Bz‐Tetrahydrochinoline und ihre Derivate.)

Abstract: v. Braun und &em k e , Bruckligdrierung d. Cinchonins usw. 177 Es war nach diesen Ergebnissen zu erwarten, dal3 die Nickeldruckhydrierung von Alkaloiden der Chininreihe in einem gewissen Umfang wohl auch zu Derivaten mit tctrahydriertem Benzolkern der Chinolinhalfte fiihren musse, und zur Prufung dieser E'rage wahlt.en wir als erstes Beispiel das Cinchonin (I). Drei Besichtspunkte waren es, die fur uns dabei im Vordergrund des Interesses standen: einmal die Frage, wie weit wohl ein sauerstoff-und stickstoffhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1934
1934
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For example, although comparison of C-9 (6 50.8) in (7) with 6 54.3 in (la) and 6 44.8 in (3a) might be taken as indicating a (15)*(16) equilibrium containing ca. 70% (15), a comparison of the C-1 shifts [S 87.5 in (7), 85.7 in (la) and 83.5 in (3a)] shows the shifts for (7) lying outside the range spanned by (la) and (3a). This is not unexpected since the additional ring fusion in (la) and (3a) must influence the average seven-membered ring conformations in the various structures and so make comparisons inappropriate.…”
Section: I ( 9 )mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although comparison of C-9 (6 50.8) in (7) with 6 54.3 in (la) and 6 44.8 in (3a) might be taken as indicating a (15)*(16) equilibrium containing ca. 70% (15), a comparison of the C-1 shifts [S 87.5 in (7), 85.7 in (la) and 83.5 in (3a)] shows the shifts for (7) lying outside the range spanned by (la) and (3a). This is not unexpected since the additional ring fusion in (la) and (3a) must influence the average seven-membered ring conformations in the various structures and so make comparisons inappropriate.…”
Section: I ( 9 )mentioning
confidence: 99%
“…The I3C n.m.r. spectrum of (7) in CDC13-CFC1, at -80 "C using gated decoupling so that no nuclear Overhauser enhancements are involved showed absorption for both conformers (15) and (16) (see Table 3), and integration of the signals from C-1, C-3, and C-5a enabled an estimate of the equilibrium position to be made as ca. 5 : 1 trans-fused (15)-cisfused (16) at that temperature.…”
Section: I ( 9 )mentioning
confidence: 99%
“…The use of higher H 2 pressures and/or elevated temperatures leads to the formation of hexa- and/or dodecahydro derivatives by partial or total hydrogenation of the quinoline moiety. The preparation of these derivatives of some cinchona alkaloids has been described. They have been tested as modifiers in the enantioselective heterogeneous catalytic hydrogenation of α-keto esters, ,, a reaction reported first by Orito et al , The presence of hydrogenated cinchona derivatives in the liquid phase during this reaction showed that the modifier may also be hydrogenated, leading to a decrease in the ee. , …”
Section: Introductionmentioning
confidence: 99%